2h+12=8h-36

Simple and best practice solution for 2h+12=8h-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2h+12=8h-36 equation:


Simplifying
2h + 12 = 8h + -36

Reorder the terms:
12 + 2h = 8h + -36

Reorder the terms:
12 + 2h = -36 + 8h

Solving
12 + 2h = -36 + 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
12 + 2h + -8h = -36 + 8h + -8h

Combine like terms: 2h + -8h = -6h
12 + -6h = -36 + 8h + -8h

Combine like terms: 8h + -8h = 0
12 + -6h = -36 + 0
12 + -6h = -36

Add '-12' to each side of the equation.
12 + -12 + -6h = -36 + -12

Combine like terms: 12 + -12 = 0
0 + -6h = -36 + -12
-6h = -36 + -12

Combine like terms: -36 + -12 = -48
-6h = -48

Divide each side by '-6'.
h = 8

Simplifying
h = 8

See similar equations:

| 5(-6x+13)=275 | | 34-35= | | -9(-6x+8)=468 | | P(2)+P(3)+P(4)+P(5)+P(6)+P(7)+P(8)+P(9)= | | -2x-6(-x-10)=16 | | 3(x-0.8)=(4x+4) | | cos(2x)+3cosx+2=0 | | 5(2-x)+5=10-4x | | cos*2x+3cos*x+2=0 | | 18+2x+0.666x=4 | | 2x+3(4x-14)=112 | | 6x+3x+7.3=5+35.2 | | 4y+x=5(2x-y) | | 6x+4(-4x-14)=-176 | | 5m^2-50m=0 | | 4x+3(-3x+13)=89 | | 7+(-5)=12 | | 0=0.3*4180*(t-20)+0.1*385*(t-400) | | x-3x+5=3x-0.5 | | 2x+3*2=5x+4 | | x-3x+5=3x-1 | | 5m(2m^2-n^3)= | | (5n-18)+(2n+12)=180 | | 3+5x=x+15 | | (4x-1)(x-9)=0 | | -3(m+4)=4 | | y=(7x+9)(x-1) | | 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x |

Equations solver categories